2020
DOI: 10.1029/2020jc016082
|View full text |Cite
|
Sign up to set email alerts
|

Moored Observations of the Savu Strait Currents in the Indonesian Seas

Abstract: The currents in the Savu Strait are observed using a subsurface mooring from November 2016 to September 2017. The mean volume transport of the Savu Strait into the Indian Ocean is estimated to be 3.0 Sv (1 Sv = 106 m3/s), with a standard deviation of 14.3 Sv. The vertical profile of the mean currents features a sandwich structure, with southwestward currents into the Indian Ocean in the upper 280 m and lower 700 m and weak northeastward currents in between. The analyses suggest that the currents flow into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The asymmetric responses of tropical North and South Pacific to climate changes suggests that the upper thermocline and sub‐thermocline of the ITF are driven by different mechanisms (M. Li et al., 2020). In addition, a recent study based on a subsurface mooring in the Savu Strait has indicated a sub‐thermocline flow from the Indian Ocean to the Indonesian Seas (Wang et al., 2020). How this Indian Ocean current exchanges with the Indonesian Seas and the North and South Pacific circulation in the sub‐thermocline layer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetric responses of tropical North and South Pacific to climate changes suggests that the upper thermocline and sub‐thermocline of the ITF are driven by different mechanisms (M. Li et al., 2020). In addition, a recent study based on a subsurface mooring in the Savu Strait has indicated a sub‐thermocline flow from the Indian Ocean to the Indonesian Seas (Wang et al., 2020). How this Indian Ocean current exchanges with the Indonesian Seas and the North and South Pacific circulation in the sub‐thermocline layer is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…After a 20‐year spin‐up period, all the runs were forced by the mean wind stress from the monthly ERA5 data from 2000 to 2020. The dynamics of the LCSM result from the westward and downward propagation of baroclinic Rossby waves from the central and eastern Pacific Ocean (Yang et al., 2020) and from the eastward and downward propagation of baroclinic Kelvin waves along the equatorial and coastal Indian Ocean (Wang et al., 2020). The LCSM can effectively reproduce the mean surface circulation of the tropical Indian Ocean and Pacific Ocean, including the Indonesian seas using the first three baroclinic modes (Li et al., 2020; Wang et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The Sumba and Savu/Dao Islands were artificially removed to reduce the loss of Kelvin waves energy along the southern boundary of Sumba Island (Yang et al, 2020) and from the eastward and downward propagation of baroclinic Kelvin waves along the equatorial and coastal Indian Ocean (Wang et al, 2020). The LCSM can effectively reproduce the mean surface circulation of the tropical Indian Ocean and Pacific Ocean, including the Indonesian seas using the first three baroclinic modes (Li et al, 2020;Wang et al, 2020). In this paper, we present only the simulations from the first two baroclinic modes since the Timor transport is mainly controlled by the first two vertical modes in the upper 400 m, as suggested by Potemra et al (2003).…”
Section: Removeislandsmentioning
confidence: 99%
“…Secondary ITF portals provide a source of fresh water, which influences stratification in the ITF (South China Sea Throughflow, Figure 1a) (Gordon et al, 2012;Wang et al, 2006;Zeng et al, 2018). The water masses from the Indonesian Seas penetrate the Indian Ocean through gaps along Sumatra to Timor, such as Timor Passage, Ombai Strait, and Lombok Strait (Sprintall et al, 2009), Sunda Strait (Susanto et al, 2016), Savu Strait (Wang et al, 2020), and Alas Strait (Susanto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%